2013
DOI: 10.1038/mi.2013.7
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D1 and aspirin-triggered resolvin D1 regulate histamine-stimulated conjunctival goblet cell secretion

Abstract: Resolution of inflammation is an active process mediated by pro-resolution lipid mediators. Since resolvin (Rv) D1 is produced in the cornea, pro-resolution mediators could be effective in regulating inflammatory responses to histamine in allergic conjunctivitis. Two key mediators of resolution are the D-series resolvins RvD1 or aspirin-triggered RvD1 (AT-RvD1). We used cultured conjunctival goblet cells to determine whether histamine actions can be terminated during allergic responses. We found cross-talk bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
134
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(144 citation statements)
references
References 25 publications
(35 reference statements)
10
134
0
Order By: Relevance
“…Resolvins have been shown to activate intracellular kinases, including Erk1/2 and Akt, which regulate cell survival and integrity (25,30,31,35). The results of the current study demonstrate that activation of ALX/FPR2 with AT-RvD1 also stimulates Erk1/2 and Akt phosphorylation in mSMG cells ( Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Resolvins have been shown to activate intracellular kinases, including Erk1/2 and Akt, which regulate cell survival and integrity (25,30,31,35). The results of the current study demonstrate that activation of ALX/FPR2 with AT-RvD1 also stimulates Erk1/2 and Akt phosphorylation in mSMG cells ( Fig.…”
Section: Discussionsupporting
confidence: 61%
“…S6). In this regard, RvD1 was recently reported to block histamine-stimulated intracellular calcium in goblet cells in a receptor-dependent manner (32), and the SPM resolvin E1 was shown to block intracellular calcium initiated by the antimicrobial peptide LLGDFFRKSKE-KIGKEFKRIVQRIKDFLRNLVPRTES (LL-37) in PMNs (33). Interestingly, another study showed that LL-37 stimulated p38 and LTB 4 formation in PMNs (34), although the signal transduction pathway leading to p38 activation was not elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Histamine itself and agonists of all four histamine receptors each stimulate goblet cell secretion and antagonists block histamine-stimulated goblet cell secretion [32]. Histamine induces mucin secretion by increasing the intracellular [Ca 2+ ] and activating extracellular regulated kinase (ERK1/2) [33, 34]. Thus goblet cells are a direct target of one of the important allergic mediators, histamine.…”
Section: Responses To Allergic Mediatorsmentioning
confidence: 99%